Calidad de vida en pacientes diagnosticados con epilepsia en el Hospital Isidro Ayora Loja, durante el periodo enero-junio 2016. - Romero Jima, Michelle Rosemary (2017)
Epilepsy is a common neurological disease in our environment, it affects quality life of people who suffer from it, due to it generates an emotional, professional, and social impact, although if the patient receives the correct medical treatment, he could endure it. The current research aims to: Identify the physical and psychological satisfaction level; ascertain the social satisfaction level and to contrast it to the level of physical, psychological and social life quality according to age group and gender. For this investigation paper, a sample of 60 patients (36 women and 24 men) was taken, in this regard, a life quality questionnaire QOLIE-31 version 1.0 was applied to all the participants with their due consent. The results were: in the male gender, physical well-being is less affected, especially in patients aged 20-25 years, while psychological and social well-being are the most affected, mainly in patients aged 31-35 years. About the female gender, psychological well-being is less affected, especially in patients aged 36-40 years, while physical and social well-being are the most affected areas in patients of the same age. As for the overall score, 30 patients registered an excellent life quality, 10 patients’ score is very good, 18 qualified as good, and 2 patients exposed a poor life quality. Keywords: Epilepsy, Physical Well-being, Psychological Well-Being, Social Well-Being